Curcumin and Viscum album Extract Decrease Proliferation and Cell Viability of Soft-Tissue Sarcoma Cells: An In Vitro Analysis of Eight Cell Lines Using Real-Time Monitoring and Colorimetric Assays. (17th February 2017) - Harati, K.; Behr, B.; Daigeler, A.; Hirsch, T.; Jacobsen, F.; Renner, M.; Harati, A.; Wallner, C.; Lehnhardt, M.; Becerikli, M.
ABSTRACT: Background : The cytostatic effects of the polyphenol curcumin and Viscum album extract (VAE) were assessed in soft-tissue sarcoma (STS) cells. Methods : Eight human STS cell lines were used: fibrosarcoma (HT1080), liposarcoma (SW872, T778, MLS-402), synovial sarcoma (SW982, SYO1, 1273), and malignant fibrous histiocytoma (U2197). Primary human fibroblasts served as control cells. Cell proliferation, viability, and cell index (CI) were analyzed by BrdU assay, MTT assay, and real-time cell analysis (RTCA). Results : As indicated by BrdU and MTT, curcumin significantly decreased the cell proliferation of five cell lines (HT1080, SW872, SYO1, 1273, and U2197) and the viability of two cell lines (SW872 and SW982). VAE led to significant decreases of proliferation in eight cell lines (HT1080, SW872, T778, MLS-402, SW982, SYO1, 1293, and U2197) and reduced viability in seven STS lines (HT1080, SW872, T778, MLS-402, SW982, SYO1, and 1273). As indicated by RTCA for 160 h, curcumin decreased the CI of all synovial sarcoma cell lines as well as T778 and HT1080. VAE diminished the CI in most of the synovial sarcoma (SW982, SYO1) and liposarcoma (SW872, T778) cell lines as well as HT1080. Primary fibroblasts were not affected adversely by the two compounds in RTCA. Conclusion : Curcumin and VAE can inhibit the proliferation and viability of STS cells.